The in-vitro and in vivo evaluations of orthopedic metal implant coated with silver composite: Potential treatment modality for implant related infection. (2019) - Nurul Hafiza, M.J.; Zulkifly, A.H.; Ibrahim, M.Z.; Munirah, S.; Mohd Toff, M.R.
Abstract: The prevalence of implant associated with infection remains high. The management of this incidence poses a major challenge in orthopedic field. Bacterial colonization and biofilm adhesion on implant may lead to infection at underlying bone and surrounding tissues. The infection risks may be overcome by application of orthopedic metallic implant coated with silver composite (OMICS) as alternative treatment of implant-infection related. The aimed of these studies were to evaluate the potential of orthopedic metal implant (plate) coated with silver composite through in vitro and in vivo experimental settings. Antimicrobial test through in vitro analysis indicates that OMICS showed excellent response against Staphylococcus aureus. The effects of OMICS on open fracture related with infection were assessed in New Zealand White Rabbit models. All rabbits were implanted with OMICS after six hours of tibial bone fracture exposure. The implanted tibia was excised en bloc and evaluated by means of microbial assessments, radiography evaluation, gross inspection and histological analysis for any infection effects. After 3 weeks of implantation, microbial analysis revealed reduced colonies were noted at study group compared to control. The radiograph, gross results and histological data collected during the experiment. There is no periosteal reaction noted at the surrounding implant area. The outcome of this study revealed positive response of the silver to prevent infection. These studies indicate that silver has it function to prevent infection. In conclusion, these values suggested that orthopedic metal implant coated with silver composite may have the potential to prevent implant related infections